2021
DOI: 10.1002/ange.202104495
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycle/Heteroallene Ring‐Opening Copolymerization: Selective Catalysis Delivering Alternating Copolymers

Abstract: Heteroatom‐containing polymers have strong potential as sustainable replacements for petrochemicals, show controllable monomer–polymer equilibria and properties spanning plastics, elastomers, fibres, resins, foams, coatings, adhesives, and self‐assembled nanostructures. Their current and future applications span packaging, house‐hold goods, clothing, automotive components, electronics, optical materials, sensors, and medical products. An interesting route to these polymers is the catalysed ring‐opening copolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 263 publications
(298 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, P(Az Bn -PA) with the highest molar mass and moderate dispersity (M n = 75.8 kDa, Đ = 1.22; Figure 2b) was obtained under this condition. Considering the cyclic topology 1 H NMR and (b) 13 C NMR spectra of P(Az Bn -PA) (entry 6, Table 1 of the copolymer (vide infra), the absolute molar mass of P(Az Bn -PA) was determined by SEC coupled with a 9-angle light scattering detector in dimethylformamide (DMF) as the eluent, showing a high molar mass of M n = 167.0 kDa with Đ = 1.22 (Figure S37). Meanwhile, copolymerization at 0.5 mol L −1 was also performed as a control (entry 10, Table 1), which produced P(Az Bn -PA) with a high alternating selectivity of 97% but a slightly lower absolute molar mass of M n = 97.7 kDa with Đ = 1.25.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, P(Az Bn -PA) with the highest molar mass and moderate dispersity (M n = 75.8 kDa, Đ = 1.22; Figure 2b) was obtained under this condition. Considering the cyclic topology 1 H NMR and (b) 13 C NMR spectra of P(Az Bn -PA) (entry 6, Table 1 of the copolymer (vide infra), the absolute molar mass of P(Az Bn -PA) was determined by SEC coupled with a 9-angle light scattering detector in dimethylformamide (DMF) as the eluent, showing a high molar mass of M n = 167.0 kDa with Đ = 1.22 (Figure S37). Meanwhile, copolymerization at 0.5 mol L −1 was also performed as a control (entry 10, Table 1), which produced P(Az Bn -PA) with a high alternating selectivity of 97% but a slightly lower absolute molar mass of M n = 97.7 kDa with Đ = 1.25.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To understand the polymerization process further, polymerization was quenched at 36% conversion. And then the product was separated into a high-molar-mass fraction and a low-molar-mass fraction by recycling preparative highperformance liquid chromatography and analyzed by 1 H NMR and MALDI-TOF MS. According to the characterization results, there was no significant difference in the microstructures of high-/low-molar-mass copolymers, both of which were cyclic alternating P(Az Bn -PA) (Figures S17, 43, and S44).…”
Section: Characterization Of P(az Bn -Pa)mentioning
confidence: 96%
See 1 more Smart Citation
“…Ring-opening copolymerization (ROCOP) may be used to access polyesters from cyclic monomers in a robust, structurally controlled manner with stereochemical, sequential, and even architectural control beyond traditional ROP techniques. Importantly, there is a vast commercial library of anhydrides and epoxides available for researchers to tune physical properties, including thermal transitions and mechanical behaviors. , The primary focus in ROCOP catalysis seemingly has been metallic complexes. , For example, the first controlled ROCOP reaction was reported by Aida and Inoue in 1985 and used an aluminum porphyrin catalyst and a tetralkyl ammonium halide co-catalyst . Since then, numerous studies have made use of various metal catalysts to produce polyesters with tailored stereochemistry, molecular weight and dispersity, composition, and even selectivity. ,,, This is likely due to the success of the Coates zinc catalyst system, which showed the ability to produce polyesters of molecular weights ranging from 10 to 55 kDa with dispersities below 1.5. Further exploration of the efficacy of zinc ligand catalysts on the ROCOP of anhydrides and epoxides was performed by the Williams group, who showed that molecular weights of 4.4–8.2 kDa were achievable within <6 h; however, the observed dispersity ranges from 1.23 to 2.75. ,, Finally, the Becker group demonstrated a magnesium-based catalyst in the ROCOP of three-dimensional (3D) printable phototpolymers intended for a host of tissue types. , Interestingly, these and similar metal catalyst species are linked to anemia, lung fibrosis, kidney disease, cardiovascular disease, respiratory cancer, nasal and lung cancers, and even reproductive toxicity, and the International Agency for Research on Cancer classifies soluble and insoluble nickel compounds as Group 1 Carcinogens to Humans …”
Section: Introductionmentioning
confidence: 99%
“…34−36 Further exploration of the efficacy of zinc ligand catalysts on the ROCOP of anhydrides and epoxides was performed by the Williams group, who showed that molecular weights of 4.4−8.2 kDa were achievable within <6 h; however, the observed dispersity ranges from 1.23 to 2.75. 25,37,38 Finally, the Becker group demonstrated a magnesium-based catalyst in the ROCOP of three-dimensional (3D) printable phototpolymers intended for a host of tissue types. 19,21 Interestingly, these and similar metal catalyst species are linked to anemia, lung fibrosis, kidney disease, cardiovascular disease, respiratory cancer, nasal and lung cancers, and even reproductive toxicity, and the International Agency for Research on Cancer classifies soluble and insoluble nickel compounds as Group 1 Carcinogens to Humans.…”
Section: ■ Introductionmentioning
confidence: 99%